Hadarat in Tual City Maluku: The Role of Arab Al-Katiri in Integration of Islam and Local Culture - Usman Nomay; Jamain Warwefubun (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This paper examines the hadarat tradition as part of integrating Islam with local culture by the Al-Katiri Arab group in Tual City. Attendance is a unique ritual that the people of Tual City carry out in celebrating religious holidays such as Eid al-Fitr, Eid al-Adha, weddings, circumcisions, and other religious activities. The community conducts friendship around the village while dancing accompanied by chanting shalawat to the Prophet Muhammad with music (tambourine) in the hadarat. This article uses a qualitative descriptive method, with observations, interviews, and documentation as the data collection techniques. This article shows that the Al-Katiri Arab community played a role in the spread of Islam in Tual City through trade routes and social and cultural approaches. The descendants of the marriage between the Arab al-Katiri group and the Kei Community of Tual City have been considered one part of the Kei community of Tual City. The information was obtained using historical research methods. Appreciating the culture of the Kei people of Tual City as a form of preaching the spread of Islam is the key to the success of the Al-Katiri Arab group living in harmony amid society with local cultural traditions.Tulisan ini mengkaji tentang tradisi hadarat sebagai bagian dari strategi mengintegrasikan Islam dengan kebudayaan lokal oleh kelompok Arab Al-Katiri di Kota Tual. Hadarat menjadi sebuah ritual unik yang dilakukan oleh masyarakat Kota Tual dalam merayakan hari besar keagamaan seperti Hari Raya Idul Fitri, Hari Raya Idul Adha, perkawinan, khitanan, dan kegiatan keagamaan lainnya. Masyarakat melakukan silaturahim mengelilingi kampung sambil menari diiringi lantunan shawat kepada Nabi Muhammad dengan musik (rebana) dalam hadarat. Artikel ini menggunakan metode deskriptif kualitatif, dengan observasi, wawancara, dan dokumentasi sebagai Teknik pengumpulan datanya. Hasil peneltian artikel ini menunjukkan bahwa komunitas Arab Al-Katiri berperan dalam penyebaran agama Islam di Kota Tual, melalui jalur perdagangan dan pendekatan sosial dan budaya. Keturunan dari hasil pernikahan antara kelompok Arab al-Katiri dengan Masyarakat Kei Kota Tual sudah dianggap sebagai satu bagian dengan masyarakat Kei Kota Tual. Informasi tersebut didapatkan dengan menggunakan metode penelitian sejarah. Menghargai kebudayaan masyarakat Kei Kota Tual sebagai suatu bentuk dakwah penyebaran agama Islam merupakan kunci kesuksesan kelompok Arab Al-Katiri hidup rukun di tengah-tengah masyarakat dengan tradisi budaya lokal.